Application of a rhodium-catalyzed cyclization cycloaddition cascade strategy to the total synthesis of (−)-curcumol. Issue 7 (30th January 2018) - Zhang, X. X.; Ko, R. Y. Y.; Xie, X. Q.; Qi, W. P.; Li, P. C.; Chiu, P.
Abstract : The first de novo total synthesis of (−)-curcumol was accomplished using a rhodium-catalyzed cyclization–cycloaddition cascade reaction as the key step. Abstract : A de novo asymmetric total synthesis of (−)-curcumol has been realized, based on a rhodium-catalyzed cyclization–cycloaddition cascade reaction as the key step to construct the tricyclic nucleus.